A SYSTEMATIC LITERATURE REVIEW ON THE INFLUENCE OF CAPTION READING THROUGH YOUTUBE 360° VIRTUAL REALITY ON ENHANCING ESL STUDENTS’ READING SKILLS AND VOCABULARY ACQUISITION - Philip, Evelyn; Mariadass, Mariann Edwina (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The use of immersive technologies and multimedia tools has created major changes to English as a Second Language (ESL) teaching methods. The systematic literature review (SLR) studies how YouTube 360° virtual reality (VR) caption reading affects ESL students' reading skills and their vocabulary acquisition. The review presents results from 35 peer-reviewed studies which were published between 2015 and 2025 according to the PRISMA 2020 guidelines. The research results show that captioned multimedia environments boost reading comprehension and vocabulary retention and student participation in learning activities. Immersive virtual reality (VR) environments provide educational experiences which enable users to acquire knowledge through their actual surroundings. The study identified three main obstacles which included cognitive overload and difficulties with access to technology and limited teaching methods. The study demonstrates that VR-enabled English as a Second Language (ESL) education needs systematic design methods and more research studies to establish effective teaching methods.